2016
DOI: 10.1523/jneurosci.0908-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulation of Myelination in Response to Visual Stimuli Alters Optic Nerve Conduction Velocity

Abstract: Myelin controls the time required for an action potential to travel from the neuronal soma to the axon terminal, defining the temporal manner in which information is processed within the CNS. The presence of myelin, the internodal length, and the thickness of the myelin sheath are powerful structural factors that control the velocity and fidelity of action potential transmission. Emerging evidence indicates that myelination is sensitive to environmental experience and neuronal activity. Activity-dependent modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
203
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(216 citation statements)
references
References 51 publications
11
203
2
Order By: Relevance
“…This is similar to what has been observed previously after knockdown of Nogo , or activation of Fyn (Czopka et al, 2013), suggesting that different signals are regulating initial myelin sheath formation and elongation. The specific molecules involved in regulating sheath length are currently unknown, but the involvement of neuronal activity has been demonstrated (Etxeberria et al, 2016;Hines et al, 2015;Koudelka et al, 2016). Such an interpretation is in line with recent experiments in zebrafish where shorter sheaths were found to be more likely to retract (Hines et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
“…This is similar to what has been observed previously after knockdown of Nogo , or activation of Fyn (Czopka et al, 2013), suggesting that different signals are regulating initial myelin sheath formation and elongation. The specific molecules involved in regulating sheath length are currently unknown, but the involvement of neuronal activity has been demonstrated (Etxeberria et al, 2016;Hines et al, 2015;Koudelka et al, 2016). Such an interpretation is in line with recent experiments in zebrafish where shorter sheaths were found to be more likely to retract (Hines et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
“…Notably, other studies have found no [47] or opposite [48] effects of neuronal activity on OPC differentiation, while others have observed differences in properties such as OL internode number [47,49••], length [48,50••,51•], or thickness [42,46,47,52]. Of these, two pioneering studies found a direct role for the synaptic activity of individual axons in regulating their selection for myelination.…”
Section: Axonal Cues For Axon Selectionmentioning
confidence: 99%
“…Conversely, blocking glutamate uptake into secretory vesicles in retinal ganglion cells in early postnatal mice increased the number of OLs that developed in the optic tract, suggesting that glutamate signalling negatively regulates OL development (Etxeberria et al, 2016). Glutamate-evoked NMDA receptor (NMDAR)-mediated signalling in OL lineage cells has been suggested to accelerate the myelination of active axons (Lundgaard et al, 2013), which might occur by NMDAR activation up-regulating glucose transport into developing OLs (Saab et al, 2016).…”
Section: Introductionmentioning
confidence: 99%